2022
DOI: 10.3390/ijms23062983
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Oral Bacteria to Commercial d-PTFE Membranes: Polymer Microstructure Makes a Difference

Abstract: Bacterial contamination of the membranes used during guided bone regeneration directly influences the outcome of this procedure. In this study, we analyzed the early stages of bacterial adhesion on two commercial dense polytetrafluoroethylene (d-PTFE) membranes in order to identify microstructural features that led to different adhesion strengths. The microstructure was investigated by X-ray diffraction (XRD), differential scanning calorimetry (DSC), and Fourier transform infrared (FTIR). The surface propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 82 publications
1
20
0
Order By: Relevance
“…The SFE surface is one of the main factors on which bacterial adhesion depends. Our previously published research determined the SFE of the tested bacterial species, and we proved that the difference between the SFE of bacteria and the surface they colonize affected adhesion [ 44 , 45 , 46 , 47 , 48 ]. Our results showed that in the presence of S. salivarius , in the initial 24-h streptococcal mixed biofilm, S. mutans was represented in smaller numbers and was a smaller proportion of the total number of bacteria.…”
Section: Discussionmentioning
confidence: 58%
“…The SFE surface is one of the main factors on which bacterial adhesion depends. Our previously published research determined the SFE of the tested bacterial species, and we proved that the difference between the SFE of bacteria and the surface they colonize affected adhesion [ 44 , 45 , 46 , 47 , 48 ]. Our results showed that in the presence of S. salivarius , in the initial 24-h streptococcal mixed biofilm, S. mutans was represented in smaller numbers and was a smaller proportion of the total number of bacteria.…”
Section: Discussionmentioning
confidence: 58%
“…Additionally, Gabrijela et al indicate that the bacteria adhesion on the membrane, which is considered a crucial initial stage for the formation of a biofilm, occurs in 4h. 51 Therefore, the elimination of residual bacteria in initial 24h was crucial for high efficacy of GBR. Based on this, we further evaluated the antibacterial efficacy of the membranes with or without MgONPs, which were co-cultured with bacteria for 24h using an MTT assay and listed it in Figure 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, implants made of natural materials such as stone, wood, horn, ivory and bone have been developed [23]. The implant utilized in this study was made of Teflon material, which is one of the most biocompatible materials used in the biomedical field; it is stable in host tissues and does not elicit an immunological response or allergic reaction; it also has excellent chemical resistance [24].…”
Section: Discussionmentioning
confidence: 99%